The Influence of Religiosity, Brand Image and Consumer Satisfaction on Repurchasing Interest of Wardah Halal Cosmetic Products - Zahrawaani, Rani (Universitas Mercu Buana, 2023)
This study aims to examine the effect of religiosity, brand image and consumer behavior on the repurchase intention of Wardah halal cosmetic products. The population in this study was the people of DKI Jakarta with a sample size of 150 which was determined using purposive sampling method. The data collection techniques were carried out using questionnaires and data analysis method using SPSS version 2.5 software. The results of this study found that religiosity had no effect on buying interest, brand image and consumer satisfaction had an effect on repurchasing interest in Wardah Cosmetics products.